Revolutionizing Mass Production: A Dual Power Portable Photographic Silkscreen Pattern Equipment - Halima A. Sahim-Sali; Joshua R. Apolinario; Spencer Vape Araneta Gregorio; Anna Rose Relativo Amalan; Kevin Maningo; Ernesto Bantug (ITEGAM-JETIA)
This research endeavors to introduce and evaluate the efficacy of a newly designed Portable Photographic Silkscreen Pattern Equipment integrated with a dual power source. Engaging a cohort of 88 participants across various departments, alongside input from eight experts in Drafting Technology at Zamboanga City State Polytechnic College, a survey questionnaire facilitated data collection via a convenience sampling approach. The study unequivocally establishes the "highly acceptable" nature of the equipment in terms of design, functionality, and portability. Noteworthy attributes include its facilitation of pattern transfer to silkscreen for efficient mass production and its adaptable use of renewable energy, rendering it operational in diverse environments, including remote areas and educational institutions. The equipment's superior portability, robust construction, and systematic wiring organization enhance its practicality. Experimentally, processing silkscreen pattern emulsion exhibits a minor time disparity between alternating current (AC) and solar battery power, with a mere one-minute difference (4 minutes on AC, 3 minutes on solar power). This study heralds a promising innovation in pattern transfer technology, poised to revolutionize mass production while championing sustainability and operational adaptability.